mFerio: The design and evaluation of a peer-to-peer mobile payment system - BALAN, Rajesh Krishna (Institutional Knowledge at Singapore Management University, 2009)
In this paper, we present the design and evaluation of a near-field communication-based mobile p2p payment application, called mFe-rio, that is designed to replace cash-based transactions. We first identify design criteria that payment systems should satisfy and then explain how mFerio, relative to those criteria, improves on the limitations of cash-based systems. We next describe mFerio's implementation and user interface design, focusing on the balance between usability and security. Finally, we present the results of a two-phase user study, involving a total of 104 people, that shows that mFerio has low cognitive load and is also fast, accurate, and easy to use - even outperforming cash in terms of speed and cognitive load in common payment situations. Copyright 2009 ACM.